Factors Associated with the Decline in Marriage Incidence Among Early Adult Women in Surabaya - Aliyyatussholihah; Budi Utomo; Endyka Erye Frety (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Marriage is a crucial phase in a woman’s reproductive life that affects physical, mental, and social well-being. In Surabaya, the number of marriages has consistently declined over the past five years, from 18,451 in 2019 to 15,870 in 2023—a decrease of approximately 13.99%. This downward trend raises concerns due to its potential implications on reproductive health, particularly when marriage and pregnancy are delayed into later age. Objectives: This study aims to analyze the factors associated with the declining decision to marry among early adult women in Surabaya. Methods: This research applied a quantitative observational approach with a cross-sectional design. The study was conducted from November 2024 to April 2025 in Surabaya. A total of 98 unmarried women aged 20–40 years were selected through purposive sampling. Inclusion criteria included being unmarried, aged 20–40, and residing in Surabaya. Respondents who were unwilling to participate were excluded. Data were collected using a questionnaire and analyzed using the chi-square test. Results: The majority of respondents (91.8%) had no plans to get married. Bivariate analysis showed that age (p-value = 0.000), income (p-value = 0.002), financial readiness (p-value = 0.015), and occupation (p-value = 0.000) had significant associations with marriage decisions. Meanwhile, education level (p-value = 0.767), family support (p-value = 0.434), and attitudes toward marriage (p-value = 0.363) showed no significant association. Conclusions: There is a significant relationship between age, economic factors, and occupation with marriage decisions among early adult women in Surabaya. No significant relationship was found between education level, family support, and attitudes toward marriage with marriage decisions in early adult women.